The Impact of Financial Inclusion and Financial Technology on Economic Growth in Indonesia - Jhoni Lumintang; Idah Zuhroh; Firdha Aksari Anindyntha (International Journal of Economics Development Research (IJEDR), 2024)
Economic growth is one of the important aspects that is of concern because it is connected to the welfare of the community and the state of a good economy, where the financial sector plays an important role in increasing economic growth. The objective of this research is to examine the effects of financial inclusion and fintech on Indonesia's economic growth. Data processing analysis in this researc using panel data regression. The results of the saving accounts and the amount of commercial bank lending have a positive and significant effect on, bank offices has a negative insignificant effect and fintech lending has a positive insignificant and effect on economic growth. To encourage economic growth, banking service providers distribute funds to the public and all industrial sectors and innovate on products and make efficiency in their services as well as analyze every risk, and for fintech companies to educate and introduce digital financial products to every element of society.